Augmented Reality as an Interactive Medium for Understanding Qur’anic Verses on the Phenomenon of Rain in Islamic Education Learning - Samsudin, Samsudin; Triase, Triase; Zufria, Ilka (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
Students’ understanding of kauniyah verses in the Qur’an, particularly regarding the phenomenon of rain, is often limited because the information presented is general and lacks integration with scientific explanations, resulting in varied interpretations. This study aims to develop an Augmented Reality (AR)-based learning media to visualize the process of rainfall based on QS. An-Nūr verse 43 and QS. Ar-Rūm verse 48. Support from tafsir ilmi and the water cycle theory is used to comprehensively understand the meaning of the verses. Students in the Information Systems Study Program are required to connect Qur’anic verses with scientific phenomena, but conventional media limit effective learning. The AR application, developed using Unity, Vuforia, and Blender, displays 3D animations of evaporation, transpiration, condensation, and precipitation phases. The development follows the Multimedia Development Life Cycle (MDLC) method, ensuring a procedural, interactive, and user-friendly approach. Testing results show that the application runs stably and effectively enhances understanding of the relationship between the verses, their interpretation, and natural phenomena in a contextual manner, implicating AR as an innovative model to enhance Qur'anic science literacy and digital learning experience.